Electrophysiology of blunted emotional bias in psychopathic personality. (9th September 2013) - Carolan, Patrick L.; Jaspers‐Fayer, Fern; Asmaro, Deyar T.; Douglas, Kevin S.; Liotti, Mario
Abstract Diminished emotional capacity is a core characteristic of psychopathic personality. We examined behavioral and electrophysiological differences in attentional bias to emotional material in 34 healthy individuals rated high or low in psychopathic traits using the short form of the Psychopathic Personality Inventory–Revised (18 high‐trait, 16 low‐trait). While performing an emotional Stroop task, high‐trait participants displayed reduced emotional modulation of the late positive potential (LPP, 400–600 ms), and early anterior positivity (EAP, 200–300 ms) amplitudes. Results suggest blunted bias to affective content in psychopathic personality, characterized by diminished early capture to emotional salience (EAP) and dampened cognitive emotional processing (LPP).